STANDAR SARANA DAN PRASARANA SESUAI DENGAN KETENTUAN STANDAR NASIONAL PENDIDIKAN (STUDI PADA MADRASAH IBTIDAIYAH HIDAYATUL FATA PUJON MALANG) - Rima Ismiatur Roikhana; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is based on the standard of facilities and infrastructure in accordance with the provisions of national education standards in MI Hidayatul Fata Pujon Malang. In MI Hidayatul Fata there are still a number of facilities and infrastructures that are inadequate or even very inadequate to support the ongoing learning process in schools. Students lack knowledge about the existence of information technology that exists in the current era, due to the absence of computer laboratory facilities so students cannot follow the advances in information technology that should be obtained at school. This research was conducted at MI Hidayatul Fata Pujon Malang. The purpose of this study was to determine the condition of facilities and infrastructure, procurement of facilities and infrastructure and the constraints of facilities and infrastructure in MI Hidayatul Fata Pujon Malang. This type of research uses a qualitative approach to the type of case study research. Data collection uses observation, interviews, and documentation. Data analysis uses data reduction, data presentation and conclusion drawing. The results of this study are the facilities and infrastructure of MI Hidayatul Fata Pujon Malang not meeting national education standards. Students lack knowledge about the existence of information technology in the current era.